Shawn, the Drosophila Homolog of SLC25A39/40, Is a Mitochondrial Carrier That Promotes Neuronal Survival - Slabbaert, Jan R. (J Neurosci, 2016)
Mitochondria play an important role in the regulation of neurotransmission, and mitochondrial impairment is a key event in neurodegeneration. Cells rely on mitochondrial carrier proteins of the SLC25 family to shuttle ions, cofactors, and metabolites necessary for enzymatic reactions. Mutations in these carriers often result in rare but severe pathologies in the brain, and some of the genes, including SLC25A39 and SLC25A40, reside in susceptibility loci of severe forms of epilepsy. However, the role of most of these carriers has not been investigated in neurons in vivo. We identified shawn, the Drosophila homolog of SLC25A39 and SLC25A40, in a genetic screen to identify genes involved in neuronal function. Shawn localizes to mitochondria, and missense mutations result in an accumulation of reactive oxygen species, mitochondrial dysfunction, and neurodegeneration. Shawn regulates metal homeostasis, and we found in shawn mutants increased levels of manganese, calcium, and mitochondrial free iron. Mitochondrial mutants often cannot maintain synaptic transmission under demanding conditions, but shawn mutants do, and they also do not display endocytic defects. In contrast, shawn mutants harbor a significant increase in neurotransmitter release. Our work provides the first functional annotation of these essential mitochondrial carriers in the nervous system, and the results suggest that metal imbalances and mitochondrial dysfunction may contribute to defects in synaptic transmission and neuronal survival. SIGNIFICANCE STATEMENT We describe for the first time the role of the mitochondrial carrier Shawn/SLC25A39/SLC25A40 in the nervous system. In humans, these genes reside in susceptibility loci for epilepsy, and, in flies, we observe neuronal defects related to mitochondrial dysfunction and metal homeostasis defects. Interestingly, shawn mutants also harbor increased neurotransmitter release and neurodegeneration. Our data suggest a connection between maintaining a correct metal balance and mitochondrial function to regulate neuronal survival and neurotransmitter release.